Mitigation of salinity impact in spearmint plants through the application of engineered chitosan-melatonin nanoparticles - Gohari, Gholamreza; Farhadi, Habib; Panahirad, Sima; Zareei, Elnaz; Labib, Parisa; Jafari, Hessam; Mahdavinia, Gholamreza; Hassanpouraghdam, Mohammad Bagher; Ioannou, Andreas; Kulak, Muhittin; Fotopoulos, Vasileios (My University, 2023)
High soil salinity represents a critical environmental constraint to crop production. In order to ameliorate the effects of salinity, a plethora of molecules have been applied and promising outcomes have been noted. The beneficial effects of chitosan (CTS) and melatonin (Mel) application, separately, have been previously recorded with respect to plant growth and productivity, leading to the hypothesis that their conjugation in the form of chitosan-melatonin nanoparticles (CTS-HPMC-Mel NPs) could lead to further enhanced performance of plants under control and stress conditions. In this regard, novel CTS-HPMC-Mel NPs were synthesized, characterized and then employed as a chemical priming agent in spearmint (Mentha spicata L.) plants 24 h prior to salinity stress imposition. As expected, salt stress negatively affected morphophysiological attributes such as plant height, leaf number, leaf fresh weight, leaf dry weight, photosynthetic pigments, Fv/Fo, and Fv/Fm. On the other hand, stress-related attributes, such as content of proline, MDA and H2O2, as well as activity of APX and GP enzymes were increased in response to salt stress. However, adverse effects of salt stress were ameliorated with Mel and CTS-HPMC-Mel NP treatments by enhancing morphological traits, proline, antioxidant enzymatic activities, as well as content of dominant constituents of essential oil profile. It is worth noting that conjugated form of Mel with chitosan, in comparison with solo treatment of Mel, was more effective in combating stress effects. To our knowledge, this is the first report to demonstrate that engineered CTS-HPMC-Mel NPs could be applied as an innovative protective agent to mitigate the effects of salinity in crop plants.
Keywords: Abiotic stress; Antioxidant enzymes; Carrier; Nanotechnology; Priming